Direct comparison of virtual reality and 2D delivery on sense of presence, emotional and physiological outcome measures - Kuhne, Caroline; Kecelioglu, Eda D.; Maltby, Steven; Hood, Rebecca J.; Knott, Brendon; Ditton, Elizabeth; Walker, Frederick Rohan; Kluge, Murielle G. (Frontiers in Virtual Reality, 2023)
Virtual-reality (VR) technology has, over the last decade, quickly expanded from gaming into other sectors including training, education, and wellness. One of the most popular justifications for the use of VR over 2D is increased immersion and engagement. However, very little fundamental research has been produced evaluating the comparative impact of immersive VR on the user's cognitive, physiological, and emotional state. A within-subject cross-over study design was used to directly compare VR and 2D screen delivery of different subject matter content. Both physiological and selfreport data were collected for scenes containing calming nature environments, aggressive social confrontations, and neutral content. Compared to 2D, the VR delivery resulted in a higher sense of presence, higher ratings of engagement, fun, and privacy. Confrontational scenes were rated as more tense whilst calming scenes were rated as more relaxing when presented in VR compared to 2D. This is a provisional file, not the final typeset article Physiological data indicated that the scenes promoted overall states of arousal and relaxation in accordance with the scene subject matter (both VR and 2D). However, heart rate (HR) and galvanic skin response (GSR) were consistently higher throughout the VR delivery condition compared to 2D, including responses during scenes of neutral and calming subject matter. This discrepancy between emotional and physiological responses for calming and neutral content in VR suggest an elevated arousal response driven by VR immersion that is independent of the emotional and physiological responses to the subject matter itself. These findings have important implications for those looking to develop and utilize VR technology as a training and educational tool as they provide insights into the impact of immersion on the user.